Small Islands, resilience and social control: how the Falkland Islands handled COVID-19. Issue 1 (2nd January 2022) - Matheson, Kate
ABSTRACT: There is already a strong literature on resilience in Island communities, and that idea has been central to understanding how Islands and Small Island Developing States (SIDS) have responded to COVID-19. However, resilience does not tell the whole story. Smaller and more isolated communities in general, and Island communities in particular, tend to have coherent and cohesive communities with strong internal control mechanisms built on shared experience and common adversity. Whilst the COVID-19 pandemic rendered small Island communities, which often lack specialist health care and robust supply chains, particularly vulnerable, there were also aspects of the small Island experience – community, surveillance and state support – that made them better able to withstand the virus. This paper, based on research interviews with participants who live or have lived in the Falklands, examines the links between COVID-19 responses, resilience and social control, in what have been some of the most challenging times for the Islands since the conflict with Argentina 40 years ago. We found that there are a number of factors particular to Island communities that have helped the Falkland Islanders to cope well with the strictures of the pandemic.